Analysis of space-time profiles of physical-chemical parameters of water quality In lake fúquene, Cundinamarca (Revista Cientifica Ingenio Magno, 2021)
Lake Fúquene is one of the most important lentic water bodies in Colombia, since it supplies water for thousands of people and multiple productive activities. However, the strong environmental degradation that it has suffered due to anthropogenic intervention, through discharges from point and non-point sources, have generated nutrient accumulation processes and hypoxic conditions that have completely altered its dynamics. In order to analyze these processes, two water quality monitoring were carried out in April and October 2019 in different geographical points of the lake evaluating the spatial variation of the concentrations of the parameters analyzed. The space-time profiles of parameters such as dissolved oxygen, pH, conductivity and ORP; as well as the concentration of pollutants such as ammonia, evidence its high state of degradation. The continuous contribution of pollutants has exceeded the capacity of the lake and the improvement processes implemented by agencies to achieve acceptable water quality conditions. In this way, it was evidenced that endangered species such as the captain fish continue to be seriously affected by their habitat depletion despite the efforts made to decontaminate this important water body.
Keywords: Spatial-temporal variations; water pollution; nutrient accumulation; fúquene; captain fish; lake management; macrophytes; sedimentation